The Effect of Social Media Marketing Activity on Consumer's Purchase Intention in Huitsportwear Products Mediated by Customer Trust - Teguh Widodo; Naufal Farras Rizqullah (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The increasing number of social media users in Indonesia has made several companies in the textile industry use social media as a medium of communication, promotion and also provide information on a product, one of which is the Huitsportwear company. Huitsportwear does marketing through Instagram social media by creating information content about products with a total of 610 posts, but Huitsportwear experienced a decline in sales and received complaints from Instagram followers about information provided on Instagram social media that was considered less informative and trustworthy, causing followers to hesitate to make purchases on Huitsportwear products. This study aims to determine how much influence social media marketing and customer trust have on consumer purchase intentions in Huitsportwear products with customer trust as a mediation variable. In this study, the method used is a quantitative method with the purpose of research, which is casual. Data collection using non-probability sampling method with convenience sampling type as many as 400 follower respondents who have purchased Huitsportwear products. This study used questionnaire data collection techniques with ordinal scales and data analysis techniques using Partial Least Square Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. This study found that social media marketing affects intention of consumer purchases and customer trust. Furthermore, customer trust affects consumer purchase intentions. Customer trust mediates the relationship between social media marketing and consumer purchase intention. The suggestion in this study is that the Huitsportwear company can create interactive and informative content about the promotion of available products and services so as to increase consumer buying interest in Huitsportwear products.